EFECTO DE LA VIGOROSIDAD DEL CORMO EN LA MULTIPLICACIÓN VEGETATIVA DEL PLÁTANO (Musa paradisiaca L.) VARIEDAD HARTÓN A NIVEL DE UMBRÁCULO - Loor Vera, Narcisa Dolores (2023)
The degree of vigor in a plant is an indication of its excellence and is used in the selection of varieties to achieve plants with ideal weight and height, thus ensuring optimal production. The main objective was to assess the effect of corm vigor on the vegetative multiplication of the Hartón banana variety in a greenhouse setting. This study was conducted at La María University Campus of the Technical State University of Quevedo. A Completely Randomized Design (CRD) was implemented, with three treatments and five replications.